Controlling Dalam Al-Quran - Yusuf Hadi Jaya; Asnil Aidah Ritonga; Isma Hayati Daulay; Sri Wahyuni; Sulasmi Sulasmi; Taufik Hidayat (Sekolah Pascasarjana Institut Agama Islam Nasional Laa Roiba Bogor, 2023)
Supervision and control in the organization is an activity that must be implemented. This activity is carried out to check the implementation of the tasks that have been set in the previous planning process. Then to find out whether there are irregularities, irregularities, or deficiencies in the implementation. If there is, revisions will be made in its implementation. So the function of controlling is to improve and to get good control, it is necessary to have a conceptual plan. The purpose of this writing is to examine the Koran's controlling issues related to their meaning and function in an institutional or non-institutional organization by using the interpretation of victory and the interpretation of al-Bayan and their correlation with management. Keywords: Controlling, Controlling, Al-Quran.